Cloud technologies LMS open EDX for organization MOOC - Nahornyi, V. V.; Nahorna, N. O.; Kaplaushenko, T. M.; Нагорний, Володимир Володимирович; Нагорна, Наталія Олександрівна; Каплаушенко, Тетяна Миколаївна (My University, 2020)
Abstract: the article analyzes the main features of LMS open edX, specifies the specifics and basic approaches to working with the interface and structural components of the system and analyzed massive open online courses (MOOCs).
Keywords: distance learning; massive online courses; MOOC; open edX; open education